Akbar and his India (Delhi : Oxford University Press, 1997)
Contributed articles on history of India during the time of Akbar, E mperor of Hindustan, 1542-1605.
Includes bibliographical references.
Keywords: Akbar, -- Emperor of Hindustan, -- 1542-1605.; Mogul Empire -- History